Profile of Patients with Complicated Chronic Suppurative Otitis Media in Dr. Hasan Sadikin General Hospital Bandung, Indonesia January–December 2011 - Fitrie Desbassarie; Arif Dermawan; Soeseno Hadi (Althea Medical Journal, 2015)
Background: The prevalence of chronic suppurative otitis media (CSOM) is still high in developing countries. According to the World Health Organization (WHO), the prevalence of CSOM is 2-4%. In 1994-1996, the prevalence of CSOM in various provinces in Indonesia is diverse, with general prevalence of 3.9%. Chronic suppurative otitis media can also lead to various complications. The objective of this study was to determine the profiles of CSOM patients with complications in Dr Hasan Sadikin General Hospital Bandung.Methods: Secondary data was obtained from 117 medical records of the period January-December 2011 in Dr Hasan Sadikin General Hospital Bandung. Out of 117 medical records, 43 medical records consisted of CSOM patients who had complications. Data of patients’demography, risk factor, chief and accompanying complaints, infected ears, pathological findings, complications, and treatments were collected and were analyzed with frequency distribution.Results: There was 36.75% CSOM patients with complications, 55.8% are male, 30.3% were 30-39 years old, 62.8% level of education of patients was primary education. Ear discharge (otorrhea) was the most common chief complaints (95.3%) and hearing loss was the most dominated accompanying symptom (53.5%), Upper Respiratory Tract Infection (URTI) was the most common risk factors. Most of the cases had unilateral complication (93%) and intratemporal (72%). Both intratemporal and extratemporal was only 26% cases. Granulation tissue was the most common intratemporal complication (32.5%). The most common procedure given was Mastoidectomy without tympanoplasty (51.2%) followed by pharmacotherapyConclusions: Percentage of CSOM with complication is still high in Dr. Hasan Sadikin General Hospital Bandung.Keywords: Chronic suppurative otitis media, complication, profile DOI: 10.15850/amj.v2n1.443